Expertise and collaboration in the geographically dispersed organization - Boh, Wai Fong (2013)
The knowledge-based view of the firm has led to greater theoretical interest in how organizations integrate knowledge resources embedded in their employees’ expertise. We examine the knowledge-integration problem in geographically dispersed professional organizations in which experts work in project teams. From consideration of coordination costs and local ties, we argue that (1) the organization will develop specialized expertise within local sites, (2) managers avoid crossing geographic boundaries to staff a project unless bringing on a distant expert helps meet customer requirements, (3) cross-site connections help less-needed members participate in dispersed projects, and (4) dispersed projects that have a better match of expertise generate higher net earnings. We tested these hypotheses using archival data and interviews in a geographically dispersed professional service organization. We examined how managers staffed 493 local and dispersed projects over a five-year period, and the financial outcomes of these projects. Managers created dispersed projects comparatively rarely; they did so when scarce expertise from other sites was needed to match customers’ project requirements. Dispersed projects garnered higher net earnings than local projects when there was a better match of scarce expertise to project requirements. However, a curvilinear relationship was observed, such that a very high percentage of dispersed experts on a project increased coordination costs and reduced net earnings. Our study extends the knowledge-based view by showing how considerations of coordination costs and social ties affect knowledge integration in the geographically dispersed organization. The study also shows, empirically, the managerial trade-offs that encourage or discourage dispersed collaboration.